Victim's Perspective of Forgiveness Seeking Behaviors After Transgressions - Martinez-Diaz, Pilar; Caperos, Jose M.; Prieto-Ursúa, Maria; Gismero-González, Elena; Cagigal, Virginia; Carrasco, Maria José (Frontiers in Psychology, 2021)
Forgiveness seeking after a relational transgression is an important aspect of relational repair from an interpersonal perspective, although it has received much less attention than the process of granting forgiveness. This research focuses on the victim´s perspective of the transgressor´s behaviors and how they are related to forgiveness and offense characteristics. This paper proposes a multidimensional concept of seeking forgiveness that includes four dimensions: apologies, restorative action, relational caring behaviors and diverting behaviors. A questionnaire for assessing these dimensions was developed and tested with a general population sample of 450 subjects. Participants recalled a specific offense and then answered a questionnaire about the perceived usefulness of different forgiveness-seeking behaviors, a forgiveness inventory and several questions regarding the characteristics of the offense (severity, intentionality and frequency). Our results support the four-factor structure of the questionnaire. As the perceived intentionality of the offense increases, behaviors that are directly related to the transgression, such as apologies and restorative actions, are experienced as less useful for forgiveness. The more hurtful the offense, the less useful the diverting behaviors are. Behavior such as apologies and restorative action are related to a lower (less) motivation for revenge, while all forgiveness-seeking behaviors are related to an increase in feelings of benevolence towards the offender.